Leave the dishes in the sink : adventures of an activist in conservative Utah - Thorne, Alison Comish (UPCC book collections on Project MUSE., 2002)
Alison Thorne provides a small-town Utah perspective on the progressive social movements that in the mid to late twentieth century dramatically affected American society. A born activist, Thorne has fought for women's rights, educational reform in public schools and universities, the environment, peace, and the war on poverty.